Investigation of the durability of Fe/N-doped mesoporous carbon nanostructure as a non-precious metal catalyst for oxygen reduction reaction in acid medium. (December 2018) - Kwak, Da-Hee; Han, Sang-Beom; Kim, Do-Hyoung; Park, Jin-Young; Ma, Kyeng-Bae; Won, Ji-Eun; Kim, Min-Cheol; Moon, Sang-Hyun; Park, Kyung-Won
Abstract: The relatively sluggish oxygen reduction reaction (ORR) and high overpotential at the cathode, compared to anode, increases the loading amount of Pt cathode catalysts. Thus, non-precious metal (NPM) catalysts such as nitrogen-doped carbon nanostructures and macrocyclic structure of transition metal and nitrogen have been studied as an alternative to conventional Pt catalyst. Previously, we reported the synthesis of a Fe/N-doped mesoporous carbon nanostructure (denoted as Fe/NC) by a template method with 5, 10, 15, 20-tetrakis(4-methoxyphenyl)-21H, 23H-porphyrin iron(III) chloride (Fe-TMPP) as a doping and carbon source. The Fe/N-doped carbon nanostructure as a NPM cathode catalyst showed the improved ORR activity owing to electrocatalytic active sites such as pyridinic and pyrrolic N states, and FeN4 macrocycles. In this study, the degradation mechanism of Fe/NC during the ORR in an acidic medium was intensively investigated by chemical acid treatment and electrochemical cycling tests in the half and unit cells in different potential ranges. The crystal and pore structures of the sample before and after the durability test were measured and compared using X-ray diffraction method and N2 adsorption/desorption analyzer. Furthermore, followed by the durability test, the surface chemical composition and state of the samples were characterized by X-ray photoelectron spectroscopy. Graphical abstract: Image 1